ChoiiEdits / Muhammad Farid Reza Mohsein - Muhammad Farid Reza, Mohsein (2020)
The business is named ChoiiEdits due to nickname given by the owner and the services provided by the company. The main purpose of the business to conduct business by providing services on editing videos and photos professionally. It is planned that the business will be located around Sg.Dua (Island) near the USM campus. This is mind is hopefully may generate income around the area as the population surrounding it mostly consist of student and residential people. The business is conducted on a rented property in the mentioned area. The team running the business will consist of five people with each running their own responsibility respectively. All equipment and furniture needed for the business are analysed with the total units and the total cost. Such examples are of are office tables, desktops, cameras and others. The total administrate budget is calculated after analysing all the equipment required. Our targeted customers are mostly consisting of students and event planners or those whom in need of our services. On promoting our business, it is concluded that various strategies will be used from digitally promoting to printed mediums. All cost of marketing is concluded at the end of the discussion. Various equipment and materials will be needed to be implemented in order to run the business. Such materials are such as fabric papers and printer ink will be used up quite often in a monthly order. Equipment such as printers, cameras, studio and others will be used to run the business. All these materials and equipment are calculated in order to list down the total cost. At the end, a financial plan is organized is order to predict the business status financially after starting out. The project implementation and sources of finance indicated the financial structure of the business. A cash flow statement is then order to identify the business future by predicted weather the business is beneficial or a deficit. In case of a deficit outcome, a new proper plan will be needed to be constructed in order to create a proper and beneficial business.